Continuous glucose monitoring among adults with type 2 diabetes receiving noninsulin or basal insulin therapy in primary care - Stephen Shields; Roy Thomas; Joy Durham; Joseph Moran; Jake Clary; Elizabeth L. Ciemins (Scientific Reports)
Abstract Rates of type 2 diabetes (T2D) continue to rise in the United States, with many patients failing to achieve glycemic targets. Primary care providers often serve as the sole clinician managing diabetes. Continuous glucose monitors (CGMs) have shown promise in diabetes management, yet their adoption in primary care settings, especially among patients with T2D not using intensive insulin therapy, remains limited. We sought to evaluate the impact of CGM use on glycemic control in patients with T2D not using insulin and those using basal but not bolus insulin in a primary care setting. CGM use was associated with a significantly greater reduction in HbA1c (-0.62%, p < 0.01) compared with matched controls at 3 months (n = 182). Patients showed improvements in time in range (39.7–61.9%, p < 0.0001), time > 180 mg/dL (60.1–37.9%, p < 0.001), time > 250 mg/dL (27.6–8.5%, p < 0.001), mean estimated glucose value (212 mg/dL to 173 mg/dL, p < 0.001) and glucose management indicator (8.39–7.46%, p < 0.001). CGM use in a primary care setting compared to usual care significantly improved glycemic control in T2D patients not on bolus insulin, irrespective of treatment with non-insulin or basal insulin. This suggests potential for broader CGM integration in primary care.